2015
DOI: 10.1007/s10508-015-0518-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Substance Use Typologies as Predictors of Sexual Risk Outcomes in African American Adolescent Females

Abstract: African American female adolescents have a disproportionate risk of sexually transmitted infections (STIs) and other adverse sexual health outcomes. Both alcohol and marijuana use have been shown to predict sexual risk among young African American women. However, no studies have attempted to differentiate alcohol and marijuana typologies use as predictors of sexual risk outcomes exclusively among adolescents who use these substances. This study compared recent alcohol and/or marijuana use as predictors of sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 35 publications
3
20
1
Order By: Relevance
“…However, alcohol use was not associated with condom use. This finding differs from the finding by Swartzendruber, Sales, and Brown (2016), who examined black female adolescents who used marijuana and or alcohol. Adolescent girls who used alcohol were less likely to use condoms.…”
Section: Literature Reviewcontrasting
confidence: 99%
“…However, alcohol use was not associated with condom use. This finding differs from the finding by Swartzendruber, Sales, and Brown (2016), who examined black female adolescents who used marijuana and or alcohol. Adolescent girls who used alcohol were less likely to use condoms.…”
Section: Literature Reviewcontrasting
confidence: 99%
“…Co-use may be particularly important to consider as use of alcohol together with marijuana may have a multiplicative effect on elevating risk [35,48]. Guo et al, [21] in one of the few longitudinal studies of urban youth, provide insight into the association of separate trajectories of alcohol and marijuana with sexual risk outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Swartzendruber et al, [48] in a rare examination of the interaction of alcohol and marijuana use, demonstrated the additional risk of co-use of alcohol and marijuana. In a sample of African American female adolescents, they found that those who used both alcohol and marijuana had an increased risk of pregnancy 18 months later compared to those who used marijuana or alcohol alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second issue is related to the risky sexual behaviors that cause many issues, problems, costs and financial burdens. In this regard, drug use has been described as the strongest cause and predictor of exposure to gonorrhea, herpes simplex virus (HSV), and HIV [30][31][32]. Since risky sexual behaviors in women drug users can be shaped based on their perceptions of social interactions, this grounded theory study will be conducted for understanding and identification of the process of risky sexual behaviors in their natural environment and social context.…”
Section: Discussionmentioning
confidence: 99%